Deep ulnar nerve compression caused by compound palmar ganglion: An unusual case of tuberculous tenosynovitis with rice body formation - Amit Kumar Vyas; Sayantani Misra (Journal of Orthopaedic Reports)
Few reports describing the localized compression of the ulnar nerve's deep motor branch have been documented in the literature. We describe a 20-year-old man who underwent successful nerve decompression and surgical exploration. The patient presented with pain along with swelling of left hypothenar eminence, accompanied by a claw hand deformity. Nerve exploration revealed rice bodies in a distended bursa compressing the intrinsic motor branch of the ulnar nerve. Rice bodies were taken out and ulnar nerve was surgically decompressed at Guyon's canal. Postoperatively, the patient was immobilized for two weeks with a splint for protection, initiated on anti-tuberculous treatment, and followed up regularly. Pressure over the ulnar nerve's deep branch may present with diagnostic difficulties. Radiological and electrophysiological examinations play a crucial role in evaluating nerve injury severity and guiding surgical intervention.